2007
DOI: 10.1159/000103600
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Fingerprints of Parasites Causing Severe Malaria in a Setting of Low Transmission in Sudan

Abstract: In this study we intended to examine the extent of genetic diversity of Plasmodium falciparum parasites causing severe malaria (SM). For this purpose, 100 parasite isolates were obtained from patients with SM and uncomplicated malaria, from an area of low and unstable malaria transmission in Sudan. The diversity of infection (DOI) was estimated by relating the number of the different parasite genotypes that were detected to the total number of parasites that were genotyped (parasite population/subpopulation). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
0
6
1
Order By: Relevance
“…Similarly, studies conducted in low endemicity areas of Honduras, French Guyana and Colombia detected the presence of two, three and five GLURP alleles, respectively ( Ariey et al 1999, Haddad et al 1999, Montoya et al 2003, Barrera et al 2010). Conversely, our observations differ from those made in high endemic areas of Asia and, more strikingly, Africa, where several groups have observed the presence of eight-20 different alleles (Snounou et al 1999, Ranjit et al 2005, A-Elbasit et al 2007, Mlambo et al 2007, Mwingira et al 2011). The limited polymorphic variation that we observed in the gene encoding GLURP may reflect the low endemicity of the area we studied.…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…Similarly, studies conducted in low endemicity areas of Honduras, French Guyana and Colombia detected the presence of two, three and five GLURP alleles, respectively ( Ariey et al 1999, Haddad et al 1999, Montoya et al 2003, Barrera et al 2010). Conversely, our observations differ from those made in high endemic areas of Asia and, more strikingly, Africa, where several groups have observed the presence of eight-20 different alleles (Snounou et al 1999, Ranjit et al 2005, A-Elbasit et al 2007, Mlambo et al 2007, Mwingira et al 2011). The limited polymorphic variation that we observed in the gene encoding GLURP may reflect the low endemicity of the area we studied.…”
contrasting
confidence: 99%
“…Previous studies of GLURP in low malaria endemicity areas have reported two alleles in Honduras (Haddad et al 1999), three alleles in French Guyana (Ariey et al 1999) and four alleles in Colombia ( Montoya et al 2003). In the high endemicity areas of Africa and Asia, anywhere from eight GLURP alleles in India to 20 alleles in Sudan have been reported (Snounou et al 1999, Ranjit et al 2005, A-Elbasit et al 2007, Mlambo et al. 2007, Mwingira et al 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported two GLURP (R2) alleles in Honduras [ 34 ], three in French Guyana [ 35 ] and each four in Colombia [ 36 ] and Brazil [ 37 ] in the area of low endemicity; however in high endemicity areas in Africa and Asia, anywhere from eight in India to twenty GLURP alleles in Sudan were reported respectively [ 18 , 20 , 21 , 38 ]. Current study found eight alleles in Group-A and nine alleles in Group-B, whereas overall ten alleles were found in the total samples compared to eight reported in Orissa [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of AAU types was calculated by dividing the number of a particular AAU type by the total number of AAU types in one block. The diversity of infection (DOI) was calculated by dividing the number of different parasite genotypes that were detected with the total number of parasites that were genotyped [ 48 ].…”
Section: Methodsmentioning
confidence: 99%